Tasawwuf: An Impetus to Islamic Revivalism in the Malay World - Abdullah, Mohd Syukri Yeoh; Yunus, Ahmad Redzuwan Mohd (ASPENSI in Bandung, Indonesia, 2011)
ABSTRACT: This working paper is a preliminary study to reveal the involvement of the Sufis in the spread of Islam, and the development of Islamic civilization in the Malay world. The study also looks at the decline in the teaching of tasawwuf and the practice of the various established Sufi orders in the region and the rest of the Muslim world today. The conduct of this study is historical in its approach. It also looks at the imperative need for the teaching of tasawwuf to be revived as to ensure that the Islamic civilization in the Malay world with all its splendour be preserved in totality, and without its authenticity being diluted. It is here presented that the endeavour would not be a futile exercise because the science of tasawwuf and the practice of the various Sufi orders appear to have a deep historical root in the Malay world. The theme of this paper is a call for the restoration of primal Islam, the worship of Allah SWT based on correct aqidah, and within the parameter of the Shariâa of Islam. And with this, the Muslims may acquire the needed spiritual strength as a defence against the continued onslaught of neo-colonialism and the uncertainties of globalisation.KEY WORDS: the Sufis, teaching of tasawwuf, Islamic civilization, globalisation, Malay world, and the restoration of primal Islam.About the Authors: Assoc. Prof. Dr. Mohd Syukri Yeoh Abdullah and Assoc. Prof.Â Dr. Ahmad Redzuwan Mohd Yunus are the Lecturers at the Department of Dakwah Studies and Leadership, Islamic Studies Faculty UKM (National University of Malaysia), 43600 Bangi, Selangor Darul Ehsan, Malaysia. E-mail address is dzuwan@ukm.myHow to cite this article? Abdullah, Mohd Syukri Yeoh & Ahmad Redzuwan Mohd Yunus. (2011). âTasawwuf: An Impetus to Islamic Revivalism in the Malay Worldâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.175-190. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980.Chronicle of the article: Accepted (February 8, 2011); Revised (March 11, 2011); and Published (April 28, 2011).